An Understanding of Volcanic Deposits With Two Dimensional Electrical Resistivity Imaging Survey at Talamau Mountain West Pasaman, Indonesia - Caesario, Dipo; Aulia, Beni; Maiyudi, Riko; Khorniawan, Wahyu Budhi; Jayanti, Anita Galih Ringga (Sumatra Journal of Disaster, Geography and Geography Education, 2024)
Understanding the distribution and characteristics of volcanic deposits is crucial for assessing geological hazards and resource potential. This study employs a two-dimensional electrical resistivity imaging (2D ERI) survey to model the subsurface structure of volcanic deposits at Talamau Mountain in West Pasaman, Indonesia. The survey was conducted to map the spatial extent, depth, and composition of these deposits, providing insights into their geophysical properties. The 2D ERI technique, which measures the electrical resistance of subsurface materials, allowed for the differentiation between various types of volcanic deposits based on their resistivity contrasts. Results from the survey reveal distinct layers of volcanic breccia, coarse tuff, fine tuff, and lava flows which are segmented by a fault that runs northeast to southeast. It is apparent in the 3D modelling results of the inversion of three 2D cross-sectional profiles that the trend in volcaniclastic materials has changed from aggradation to progradation. The integration of 2D ERI data with 3D geological modelling and stratigraphic analysis enhances our understanding of the volcanic history and subsurface complexity of Talamau Mountain. This approach not only aids in volcanic hazard assessment but also contributes to the broader geophysical knowledge of volcanic terrains for geologists and hazard mitigation planners in Talamau volcanic regions.